THE INFLUENCE OF GREEN MARKETING STRATEGY TOWARDS PURCHASING DECISIONS WITH BRAND IMAGE AS AN INTERVENING VARIABLE ON AQUA BOTTLED DRINKING WATER IN MANADO - Rambing, Precylia R.; Tumbel, Altje L.; Tawas, Hendra N. (FEB Universitas Sam Ratulangi Manado, 2015)
The change and development of technology in the processing of natural resources often negatively affect the condition of the earth. Consumers realize the occurring situation and begins to be selective in determining which products will be used, which products are environmentally friendly. The company also seeks to implement environmental issues as one strategy in its marketing. This research aims to find out the influence, either directly or indirectly, of green marketing and brand image towards purchasing decision. The research method is associative. The research instrument uses Likert scale and method of analysis uses Path Analysis. The sample research sample is as much as 120 respondents. The result shows that green marketing does not directly influence buying decision. Green marketing affects indirectly toward purchasing decisions with the brand image as the intervening variable. The management of the company should pay attention to Aqua?s green marketing of their Bottled Drinking Water products so that consumers will not hesitate to consume products that are environmentally friendly. Keywords: green marketing, brand image, purchase decision